Analisis Pengaruh Brand Image dan Desain Produk terhadap Minat Membeli Konsumen pada Toko Sepatu Bata Pancing MMTC Kota Medan - Ronaldo Pardede; Sabda Dian Nurani Siahaan (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence of Brand Image and Product Design on Consumer Purchase Interest at Bata Pancing Shoes Store MMTC Medan City. The method used is a quantitative approach with probability sampling technique, with the research population being shop visitors located at Jl. Williem Iskandar, Sidorejo, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. The data were analyzed using SPSS software version 26. The results showed that Brand Image (X1) had a positive and significant effect on Consumer Purchase Interest (Y) with a coefficient of 0.645 and a significance value of 0.000. Meanwhile, Product Design (X2) also had a positive and significant effect with a coefficient of 0.171 and a significance value of 0.007. Simultaneously, both variables contributed 73.8% to Consumer Purchase Interest, while 26.2% was influenced by other factors outside this study. Thus, Bata Pancing Shoes Store is advised to strengthen Brand Image and develop Product Design to increase Consumer Purchase Interest.